Clinical significance of supplementary innervation of the lower incisor teeth: a dissection study of the myelohyoid nerve - Madeira, M. C.; Percinoto, Célio [UNESP]; Silva, M. G M (Elsevier, 1978)
In view of the relevance of the mylohyoid nerve to clinical difficulties in achieving deep analgesia of the lower incisors, a dissection study was undertaken. Dissections from 29 adult cadavers of both sexes were studied with the aid of a dissecting microscope. The following observations were made: a supplementary branch of the mylohyoid nerve entered the mandible through accessory foramina in the lingual side of the mandibular symphysis in 50% of the cases; it generrally arose from the right side (76.9%) and entered the inferior retromental foramen (84.6%); the mylohyoid nerve branch either ended directly in the incisor teeth and the gingiva or joined the ipsilateral or contralateral incisive nerve. In view of this information concerning the high incidence of possible involvement of the mylohyoid nerve in mandibular sensory innervation, it is advisable to block it whenever intervention in the lower incisors is indicated. Routine mylohyoid injection is recommended after mental nerve block. If the inferior alveolar nerve is chosen for anesthetic purposes, additional mylohyoid injection should be given only if pain persists. The mylohyoid injection should be given at the inferior retromental foramen on the median aspect of the inferior border of the mandible through extraoral approach.
Keywords: autopsy; innervation; lower incisor; mylohyoid nerve; nervous system; normal human; peripheral nervous system; tooth; Adult; Anesthesia, Dental; Female; Human; Hyoid Bone; Incisor; Injections; Male; Mandible; Mandibular Nerve; Mouth Floor; Nerve Block